Designing and Fabrication of Cost Effective Electric Go-Kart - Abhijith C S; Joly.M; Vivek P V; Adarsh C S; Vaishnavi K S; Arjun Krishna V G (International Journal of Scientific Research in Science and Technology, 2024)
There are many motor sports in the world. Bikes, Car, Formula one are examples of them. The drivers in this are very professional and accurate. They can drive it very fast. But there are also motor sports which don’t need professional drivers and need no great speed. The vehicles used are also very cheap. Such a motor sport is Go-karting. They resemble to the F1 cars but it is not as faster as F1 and also cost is very less. The drivers in go-karting are also not professionals. Even children can also drive it. They are widely used in racing in US and also they are getting popular in India. This work presents the design and analysis of a cost effective electric motor powered kart. The main aim of this paper is to reduce the usage of organic fuel powered vehicles and to design a vehicle which works efficiently in the emerging electric vehicle sector. The design is made keeping in mind the high strength of vehicle which can sustain more weight and provide the best facilities at a low cost. In order to maintain the speed levels of the kart, seamless decision was made in motor selection. Alternate materials have been applied in the kart to reduce both static and dynamic forces in pursuance of improving the efficiency and performance of the kart. Detailed design of subsystems like chassis frame, steering system, electrical power train and braking mechanism has been done effectively. The main focus of the frame design was on the stability of the kart and safety of the driver.
Keywords: Electric go-karts; Hall effect sensor